Comprehensions of Controlling in Bulgarian Scientific Literature - Angelova, Antoaneta (Research Papers, 2024)
This article clarifies the concept of “controlling” in the Bulgarian scientific literature, found in the world database Google Scholar for 2018 – October 2023. The article is based on an analytical review. The research toolkit covers methods of analysis and synthesis and a structured approach to searching scientific literature. The sample of the study is 16 sources. The research results conclude that it is a modern management concept aimed at adapting the organization to the rapidly changing conditions of the external environment. The main recommendation of the author of the article is the introduction and confirmation of controlling as a “meta” function in the management practice of Bulgarian organizations aimed at their strategic development.